Powidoki wiersza. Eksperyment lektury poezji Bolesława Leśmiana - Kłosowski, Mateusz (Przestrzenie Teorii, 2019)
The article shows how the visual-painting category of afterimage, which derives from Władysław Strzemiński’s concept, functions at the level of literature (in the poetry of Bolesław Leśmian) and literary studies, as an attempt to apply art concepts to the interpretation of verse. The text is experimental in that it suggests using afterimage as a tool of cognitive philosophy that enables the new meanings to be highlighted in reading the poetic works of Leśmian and in establishing the relations between the visual and the word.